Anti-corruption mechanism in Ukraine: content actualization under the conditions of normative innovations - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V. (Universidad del Zulia Maracaibo : Venezuela, 2021)
The aim of the investigation was to determine the most appropriate avenues for further implementation of the European concept of anti-corruption. To carry out this article, general and special research methods have been applied, such as systems analysis, dialectical, formal logical and structural functional methods, as well as a series of empirical methods. Statistical analysis has been used to demonstrate anti-corruption measures, undertaken in 2016 - 2020. The anti-corruption mechanism has been analyzed through the prism of combined institutional and instrumental systems, with the aim of preventing corruption. The priorities for transforming the anti-corruption mechanism have been defined as follows: (a) increased accountability for corruption offences; (b) introduction and appropriate application of corruption detection tools. It is concluded that the current trend demonstrates a decline in the implementation of anti-corruption preventive tools in Ukraine due to the following factors: change of the vector of public interest towards compliance with antiCovid-19 measures, destabilization of authority and lack of collaboration between authorized subjects in solving corruption problems.

Метою розслідування було визначити найбільш прийнятні шляхи подальшої реалізації європейської концепції боротьби з корупцією. Для написання даної статті були застосовані загальні та спеціальні методи дослідження, такі як системний аналіз, діалектичний, формально-логічний та структурно-функціональний методи, а також ряд емпіричних методів. Для демонстрації антикорупційних заходів, здійснених у 2016-2020 роках, використано статистичний аналіз. Антикорупційний механізм проаналізовано через призму комбінованих інституційних та інструментальних систем з метою запобігання корупції. Пріоритети трансформації антикорупційного механізму визначені таким чином: (а) посилення відповідальності за корупційні правопорушення; (b) впровадження та належне застосування засобів виявлення корупції. Зроблено висновок, що поточна тенденція демонструє зниження впровадження інструментів антикорупційної превенції в Україні через такі чинники: зміна вектору суспільних інтересів у бік дотримання заходів протидії Covid-19, дестабілізація влади та відсутність співпраці між уповноваженими суб'єктами у вирішенні корупційних проблем.
Kivalov S. V. Anti-corruption mechanism in Ukraine: content actualization under the conditions of normative innovations / S. V. Kivalov // Cuestiones Políticas. - Vol. 39. - No. 71. - Universidad del Zulia Maracaibo : Venezuela, 2021. - P. 972-985.
Keywords: anti-corruption mechanism; measures to combat corruption; institutional system; public sector; lifestyle of the reporting subjects; антикорупційний механізм; заходи протидії корупції; інституційна система; державний сектор; спосіб життя суб'єктів звітності; Research Subject Categories::LAW/JURISPRUDENCE